СОЦИАЛЬНО-ПСИХОЛОГИЧЕСКИЕ МЕХАНИЗМЫ МЕЖЛИЧНОСТНОГО ВЗАИМОДЕЙСТВИЯ В ГАНДБОЛЬНЫХ КОМАНДАХ - Расулов, З.П.; Казакбаева, Г.У. (SCIENCE and SOCIETY, 2025)
The article examines socio-psychological factors of interpersonal interaction in handball teams.
Keywords: interpersonal relationships; handball; sport psychology; team cohesion; team communication; coach-athlete relationship; sports team